Foraminiferal Biostratigraphy of the Eocene Kirthar Formation, western Sulaiman Fold-Thrust Belt, Balochistan, Pakistan - Babar, Najeebullah; Mohibullah, Mohibullah; Kasi, Aimal Khan; Ali, Nowrad; Khan, Abdullah (Journal of Himalayan Earth Sciences, 2018)
Kirthar Formation outcrops in the Quetta District in the western Sulaiman Fold-Thrust Belt has yielded rich and moderately diverse larger benthic foraminifera (LBF), comprising of thirty species from twenty- three different genera. On the basis of these identified assemblages, three Tethyan shallow benthic zones (SBZ 18- SBZ 20) spanning late Middle to Late Eocene are recognized. The SBZ 18 is characterized by the appearance of Pellatispira madaraszi, Nummulites striatus, Borelis vonderschmitti and species of Alveolina and Heterostegina. The boundary between Middle and Late Eocene is recognized by the appearance of Nummulites fabianii and Spiroclypeus. Fauna of the Kirthar Formation show some similarities to the West Tethys and other parts of eastern Tethys, facilitating a wide geographic stratigraphic correlation.